Recurrent Abdominal Pain in Peutz-Jeghers Syndrome: A Case Report - Anwar, Sayeeda; Kamal, Nusrat; Khanom, Rokeya; Roy, Subrota Kumar; Kabir, Farzana; Saha, Ramkrishna (Journal of Bangladesh College of Physicians and Surgeons, 2019)
Peutz-Jeghars Syndrome (PJS), also known as peri-orificial lentiginosis, is a condition of autosomal dominant inheritance. Here, mutation localized at (19p13.3) LKB1/ STK11. It is characterized by presence of mucocutaneous pigmentation and gastrointestinal (GI) hamartomatous polyps. This case of PJS, is a 7 year old girl who came with recurrent vomiting and abdominal pain for 1 year and weight loss for 8 months. She had multiple black pigmentation over lips and buccal mucosa. Endoscopy revealed multiple polyps in stomach and duodenum. Besides supportive management, polyps were removed by surgical intervention. Biopsy of these polyps showed hamartomatous type. Post operative period was uneventful. She recovered well. So far there was no recurrence of pain. She is on regular follow up. J Bangladesh Coll Phys Surg 2019; 37(3): 160-164